Problematika Pembelajaran Bahasa Arab pada Mahasiswa Lulusan Umum di Prodi Pendidikan Bahasa Arab Universitas Pendidikan Indonesia - Khasanah, Luthfia Nur; Tantowi, Yusuf Ali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine the problems of understanding Arabic language learning in general graduate students of Arabic language education study programs. This study uses qualitative research methods with descriptive analysis and data collection techniques in the form of interviews and literature. The results of this study are 1. linguistic problems that general graduate students find challenging to understand Arabic learning material, both from memorizing vocabulary, grammar, or Nahwu and Sharaf and having difficulty understanding the material being studied. 2. Non-linguistic problems The problems that occur with general graduate students are for motivation. Students have the motivation to want to understand learning Arabic. However, learning material in class is considered difficult to understand because these students do not understand the methods used. Then the external environment of students who are not fluent in using Arabic affects the fluency of students learning Arabic.